Reducing Capsular Contracture Formation in Breast Augmentation with Silicone Implants: Experimental Study on Rats - Nadia Aladari; Madalina M. Palaghia; Ana-Maria Trofin; Elena Cojocaru; Carmen Ungureanu; Victor Ianole; Eugenia Morosan; Cristian C. Budacu; Theodor C. Motruc; Mihaela Pertea; Teodor Stamate (Applied Sciences, 2022)
Silicone implants are frequently used for breast augmentation and reconstruction. However, late complication, such as capsular contracture, remain the most important side effect. In this study we compare different methods for reducing the inflammatory reaction around the silicone implant by introducing one microtextured breast implant in wistar rats. The rats were dividing in 4 groups: the first one was the control group that received untreated implant; in the second we used silicone implants impregnated with rifampin solution, the third one had implant combined with intramuscular dexamethasone injection and the last one had silicone implant associated with autologous centrifuged fat introduced in the implant pocket. The implants and the capsular tissue surrounding were removed after eight weeks. Capsule samples were submitted to histological evaluations. The present study demonstrated that fat grafting may have a role in reducing and preventing capsular contractures after breast augmentation with silicone implants by decreasing the inflammatory process.